Does Customer Identity Bridge The Gap Between Company’s Green Market Orientation And Customer Perceived Value Proposition? - Samarasinghe, G.D.; Ahsan, Fazeela Jameel (My University, 2011)
This conceptual paper addresses the value-action gap in green consumer behavior which implies that preference for green products does not always lead to actual purchase behavior. Based on rigorous analysis and synthesis of literature on sustainable consumption, green consumerism, identity theory and customer perceived value, it develops conceptual framework that address process through which green market orientation contributes to customer perceived value creation and develops a set of testable propositions that illustrate customer’s desired self and social identities intervenes the link between firm’s green market orientation and firm created utilitarian, emotional and social values perceived by target customer. In postmodern literature, consumption is highly viewed as a process of creating identity of consumers. Hence, the paper adds some novelty to green marketing literature by expanding its domain to identity construction through green consumption. However, these propositions need to be empirically tested. This conceptualization has implications for practicing marketers to craft greener marketing strategies to win competitive advantage as well as promote environmental sustainability.